2011
DOI: 10.1111/j.1526-100x.2010.00687.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing Disturbance, Seeding Time, and Soil Amendments for Establishing Native Warm‐Season Grasses in Non‐Native Cool‐Season Pasture

Abstract: Incorporating native C4 grasses into pastures dominated by C3 grasses can augment tallgrass prairie restoration efforts while improving pasture production. We examined grazing and burning disturbances to promote the establishment of native C4 grasses sown in fall and spring into existing C3 pastures. A second objective was to test the role of resource availability on C4 grass establishment by manipulating inorganic nitrogen (N) availability within each seeding time and management treatment combination. We dril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…Observations of different competitive ability of native late‐seral species over non‐native early‐seral species (mostly invasive plants) based on their different tolerance of low soil nutrient content (Morghan & Seastedt ; Craine ; Doll et al . ; Eldridge, Redente & Paschke ; Cleland, Larios & Suding ) has led to nitrogen immobilization through carbon amendment as a possible management technique. Carbon amendments increase soil microbial biomass (Zink & Allen ; Eschen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Observations of different competitive ability of native late‐seral species over non‐native early‐seral species (mostly invasive plants) based on their different tolerance of low soil nutrient content (Morghan & Seastedt ; Craine ; Doll et al . ; Eldridge, Redente & Paschke ; Cleland, Larios & Suding ) has led to nitrogen immobilization through carbon amendment as a possible management technique. Carbon amendments increase soil microbial biomass (Zink & Allen ; Eschen et al .…”
Section: Introductionmentioning
confidence: 99%
“…such as herbivory and granivory (Jackson and Bartolome, 2002 amendments (e.g., Bonebrake et al, 2011;Doll et al, 2011;Kulmatiski, in the Carrizo Plain, and native plant cover has declined (Schiffman, 1994;133 Q6 Germano et al, 2001).…”
mentioning
confidence: 98%
“…The prevailing theory is that nutrient limitation creates an ecological filter that excludes the more generalist invasive species but allows more specialized native species to thrive under conditions of reduced competition(Corbin and D'Antonio, 2004;Nuttle, 2007). In response to this pattern, recent studies have investigated the potential role of soil amendments for increasing native plant restoration success (e.g.,Bonebrake et al, 2011;Doll et al, 2011;Kulmatiski, 2011). Most commonly, soil nitrogen availability is reduced by adding carbon to the soil in the form of wood chips or glucose 419(Stromberg et al, 2007).…”
mentioning
confidence: 99%
“…As the pre-existing sward of Austrostipa was similarly C3, this could reflect inadequate distinction in resource use among resident and new species, consistent with the concept of limiting similarity (Funk et al 2008). While resource capture is seldom spatially or temporally complete (Davis et al 2000), some form of disturbance is often needed to increase resource availability and reduce risk of establishment failure (Luken 1990;Doll et al 2011). However, an earlier study observed similarly poor recruitment of Poa in C4 Bothriochloa swards, as well as high recruitment of C4 Themeda in these C4 swards .…”
Section: Native Grass Establishmentmentioning
confidence: 97%